An Experimental Study on Solidifying Municipal Sewage Sludge through Skeleton Building Using Cement and Coal Gangue. (16th February 2017) - Yang, Jiankang; Lu, Haijun; Zhang, Xiong; Li, Jixiang; Wang, Weiwei
Abstract : The municipal sewage sludge typically has very high water content and low shear strength. Conventional methods of lime and cement solidification of municipal sewage sludge often suffer high cost, significant drying shrinkage, frequent cracking, high hydraulic conductivity, and low strength. To overcome these shortcomings, in this paper a skeleton-building method was used to solidify municipal sewage sludge in which coal gangue, cement and clay, and fiber were used as skeleton materials, cementation materials, and filling materials, respectively. Comprehensive laboratory tests including cracking, nitrogen adsorption, triaxial shearing, and permeability tests were performed to determine cracking, pore structure, shear strength, and hydraulic conductivity of municipal sewage sludge solidified with different proportions of coal gangue, cement, fiber, and clay. Based upon the experimental results, the mechanisms of the skeleton building using cement and coal gangue were discussed and factors controlling the mechanical and hydraulic behavior of the solidified soils were analyzed at both microscopic and macroscopic levels. Based upon the test results and analyses, recommendations were made for solidifying municipal sewage sludge through skeleton building using cement and coal gangue. The solidified soils have high soil strength, high resistance to cracking, and low hydraulic conductivity which are sufficient for being used as landfill liner.